Could the stability and growth pact be substituted by the financial markets - Terezie Výprachtická (Charles University in Prague, Institute of Economic Studies (IES), 2010)
In the discussions of the need for fiscal rules and their usefulness in a monetary union researchers have not agreed on whether the financial markets have a sufficiently disciplining effect on the governments, which would mean that the fiscal rules are not necessary. This paper investigates whether the European Union's main fiscal rule, the Stability and Growth Pact, could be substituted by the financial markets, taking into account also the effects of the latest financial and economic crisis. Our findings suggest that there is certain interaction between the financial markets and the governments' decisions on the fiscal policies and that this reaction has become stronger after the beginning of the crisis. However, the institutional setup and market conditions in the European Union are such that this interaction is biased and thus we conclude that the Union needs to have fiscal rules.
Keywords: C23; E44; E62; H62; H74; H87; 330; European Economic and Monetary Union; Stability and Growth Pact; Financial markets; Fiscal rules; Eurozone; Europäischer Stabilitätsmechanismus; Finanzmarkt; Finanzpolitik; Regelbindung; EU-Staaten